Novel member of the zinc finger superfamily: A C2-HC finger that recognizes a glia-specific gene. - Kim, J G (1992)
A novel member of the zinc finger superfamily was cloned by virtue of its binding to cis-regulatory elements of a glia-specific gene, the myelin proteolipid protein (PLP) gene. Named MyTI (myelin transcription factor I), this gene is most highly transcribed in the developing nervous system, where expression precedes induction of its presumptive target, PLP. Low levels of MyTI transcripts can be detected in nonneural tissues only by polymerase chain reaction analysis. Zinc is a necessary cofactor for DNA binding of MyTI, as the zinc-chelating agent 1,10-orthophenanthroline eliminates binding activity. Zinc may stabilize the DNA-binding domain of MyTI by coordinating three cysteine and one histidine residue in a Cys-X5-Cys-X12-His-X4-Cys (C2-HC) arrangement. The MyTI protein has six fingers of the C2-HC class arranged in two widely separated clusters. These two domains of DNA binding can function independently and recognize the same DNA sequence, suggesting that MyTI may contribute to the higher-order structure of a target promoter by simultaneously binding both proximal and distal sites. The six fingers are highly conserved, suggesting that they arose from successive duplication events, while the linker regions diverge in size and sequence. Both amino acid sequence comparisons and secondary-structure predictions indicate that the C2-HC fingers of MyTI do not resemble the zinc-mediated loops of C2-H2 fingers, C2-C2 fingers, or Cx clusters. MyTI may therefore be the prototype of a new structural family of zinc-stabilized DNA binding proteins.